2011
DOI: 10.1098/rspb.2010.2233
|View full text |Cite
|
Sign up to set email alerts
|

History matters: ecometrics and integrative climate change biology

Abstract: Climate change research is increasingly focusing on the dynamics among species, ecosystems and climates. Better data about the historical behaviours of these dynamics are urgently needed. Such data are already available from ecology, archaeology, palaeontology and geology, but their integration into climate change research is hampered by differences in their temporal and geographical scales. One productive way to unite data across scales is the study of functional morphological traits, which can form a common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 94 publications
(120 reference statements)
0
62
0
Order By: Relevance
“…These results document this pattern for the first time in fossil marine mammal assemblages. Because our results showed that the taxonomic components of each assemblage involved taxa that were largely unrelated to one another (i.e., none were sister taxa), we argue that the iterative evolution of multispecies dugongid communities demonstrates the merit of extending questions about generality of community assembly [29], [30] into the fossil record of marine mammals, paralleling ongoing efforts with the comparatively denser and better-studied fossil record of terrestrial mammals [31][38]. Although we relied on ecomorphologic and body size proxies to detect the resource partitioning described for fossil dugongid communities, the application of other methods could possibly yield additional information.…”
Section: Discussionmentioning
confidence: 87%
“…These results document this pattern for the first time in fossil marine mammal assemblages. Because our results showed that the taxonomic components of each assemblage involved taxa that were largely unrelated to one another (i.e., none were sister taxa), we argue that the iterative evolution of multispecies dugongid communities demonstrates the merit of extending questions about generality of community assembly [29], [30] into the fossil record of marine mammals, paralleling ongoing efforts with the comparatively denser and better-studied fossil record of terrestrial mammals [31][38]. Although we relied on ecomorphologic and body size proxies to detect the resource partitioning described for fossil dugongid communities, the application of other methods could possibly yield additional information.…”
Section: Discussionmentioning
confidence: 87%
“…ANCASH: Huaraz , Tullparaju, 4300, -9.03; -77.67 (FMNH 81371, 81373) [1]; Huari , Canrash, 4370 m, -9.68; -77.05 (mcp 54, 55, 56, 59, 63) [2]; Huari , Chacacmonte, 4220 m, -9.68; -77.11 (mcp 34, 35, 36, 42) [3]; Huari , Jupro, 4000 m, -9.59; -77.08 (mcp 67, 68) [4]; Huari, Paccha, 4240 m, -9.63; -77.12 (mcp 04, 05, 11, 15, 18, 20) [5]; Huari , Pumahuain, 4250 m, -9.66; -77.13 (mcp 24) [6]; Huari , Río Mosna, between Chavín and San Marcos, 3100 m, -9.55;-77.17 (FMNH 129213, 129215, 129219, 129225) [7]; Santa , Macate, 2250 m, -8.77; -78.08 (FMNH 20899, 20905, 20909) [8]. …”
Section: Appendix – Specimens Used In the Analysismentioning
confidence: 99%
“…For example, across species there is a negative correlation between body size and environmental temperature (Bergmann’s rule [4]) and an association in mammals between precipitation and high degree of hypsodonty in species inhabiting arid and grassy regions [5,6]. However, localized phenotypes may not necessarily be observed within a species, even if populations occur across steep environmental gradients and disparate ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…These traits must be easily measured, their structure must be closely related to their function, and they must directly interact with their environment (Eronen et al 2010). Ecometrics has come into the spotlight as a way to measure both biodiversity (Roberts and Moore 1997;Alfaro et al 2007;Anderson 2009and effects of climate change in many different types of organisms (Eronen et al 2010;Polly et al 2011). Ecometrics can also be used to examine how morphology shapes ecological communities and how niches are partitioned in closely related sympatric species.…”
Section: Introductionmentioning
confidence: 99%